Using the Callback to eliminate sub-routing in a vehicle routing problem with simultaneous pick-up and delivery of multiple products - Lopes, Roza Maria Zoellner; Doehnert, Ruany Batista Leite; Loch, Gustavo Valentim; Pécora Junior, José Eduardo; Scarpin, Cassius Tadeu (Revista Gestão da Produção Operações e Sistemas, 2020)
The Vehicle Routing Problem with simultaneous pick-up and delivery of multiple products (VRPSPD) is addressed in practice when just collecting the product is not sufficient to meet the client’s requirements. This article aims to apply Callback available in Gurobi software to the elimination of sub-routes in a VRPSPD using lazy constraints. In order to test the efficiency of the proposed method, we first solved the relaxed problem of Mixed Integer Programming (MIP), and then the same problem was solved using the Callback. The performed tests show that the use of Callback is efficient leading to time reductions in runtime to prove the optimality.